Role Of Road Safety System And Its Elements In Ensuring Road Safety - Murotbek Boydadaev; Ovlakulov Ikrom (Peerian Journals Publishing, 2025)
The problems and features of road traffic are determined, first of all, through the system "Car-driver-road-pedestrian". They, in turn, act in the environment
Keywords: Car; driver; environment